Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai Kantor Pelayanan Pajak Pratama Bandung - D, Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2022)
This study aims to determine: (1) The effect of the work environment on the performance of KPP Pratama Bandung Cicadas employees, (2) The effect of work motivation on the performance of KPP Primary Bandung Cicadas employees, (3) The influence of the work environment and work motivation on the performance of KPP Pratama Bandung Cicadas employees . This research is a research using a quantitative approach. The sample in this study were the employees of the Bandung Cicadas Pratama tax office, totaling 50 employees. Data collection used a questionnaire while data analysis used multiple regression analysis.The results of this study indicate that the Work Environment and Work Motivation simultaneously have the same effect on Employee Performance. While partially only work motivation variables that affect employee performance.